Modulation of Gut Microbiota, and Morphometry, Blood Profiles and performance of Broiler Chickens Supplemented with Piper aduncum, Morinda citrifolia, and Artocarpus altilis leaves Ethanolic Extracts - Paredes-López, Daniel Marco; Robles-Huaynate, R. A.; Soto-Vásquez, Marilu Roxana; Perales-Camacho, Rosa Amelia; Morales-Cauti, Siever Miguel; Beteta-Blas, Xiomara; Aldava-Pardave, Uriel (Frontiers in Veterinary Science, 2024)
Bioactive plants such as P. aduncum, M. citrifolia, and A. altilis might improve intestinal health as an alternative to antibiotic growth promoters. The objective of this study was to determine the effect of the ethanolic extracts (EEs) of these plants on the intestinal health of broiler chickens. Cobb 500 chickens (n = 352) were distributed into eight treatments with four replicates and 11 chickens each. T1 received a base diet, and T2 received a base diet with 0.005% zinc bacitracin. T3, T5, and T7 were supplemented with 0.005% of P. aduncum, M. citrifolia, and A. altilis EE in the diet while T4, T6, and T8 with 0.01% of the extract. The EEs were supplemented with drinking water from 1 to 26 days of age. The following parameters were evaluated: hematological profiles at 28 days of age, blood metabolites profiles at 14, 21, and 28 days; Escherichia coli, Staphylococcus aureus, and Lactobacillus sp. abundance in the ileum mucosa and content at 21 and 28 days, and histomorphometry of the duodenum, jejunum, and ileum mucosa at 14, 21, and 28 d. Final weight (FW), weight gain (WG), feed intake (FI), and feed conversion rate (FCR) were evaluated at seven, 21, and 33 days of age. M. citrifolia and A. altilis EE at 0.01% increased blood glucose levels at 21 and 28 days of age, respectively, and P. aduncum and M. citrifolia EE at 0.01% increased triglycerides at 28 days of age; in addition, this EE did not have any effect on the AST and ALT profiles. The depths of the Lieberkühn crypts and the villi length to the crypt’s depth ratio increased with age on supplementation with 0.01% M. citrifolia and A. altilis EE at 21 days of age (p < 0.05). In addition, the depth of the crypts increased at 28 days of age (p < 0.05) in chickens supplemented with 0.01% A. altilis EE. The 0.01% M. citrifolia EE in diet decreased in the Staphylococcus aureus population in the ileal microbiota (p < 0.05). The FW and WG during the fattening and in the three stages overall increased, and the FCR decreased; however, the FI and the carcass yield did not change in the broiler chickens supplemented with 0.01% M. citrifolia EE (p < 0.05). Conclusively, the M. citrifolia EE at 0.01% of the diet improved intestinal health and thus the performance indices of the broiler chickens and did not have a detrimental effect on any of the parameters evaluated, so it is postulated as a potential alternative to AGP in poultry.